Systèmes écrivants et répartition des rôles interactionnels - Krafft, Ulrich; Dausendschon-Gay, Ulrich (Wydawnictwo Naukowe UAM, 2000)
In cooperative writing two or more interacting persons work together to write a common text. After several case studies with unplanned writing interactions, in an experiment we asked 17 dyads to compose a recipe for mousse au chocolat. In the first part of the essay we show that one can describe the cooperating dyads as writing systems with specific properties, the interacting persons as agents of the system. After that we ask how far the writing system determines the activities of its agents and to what extent the distribution of activities, conversely, follows the wishes and preferences of those interacting. We also examine whether one can speak of a “writing style” of the writers working together in the writing system.
Writing systems and repartition of interactional roles